Prinsip kerjasama dalam wawancara di acara televisi “Quotidien” - Armry Zai, Saga; Ismail, Subur; Andika, Yunilis (Franconesia, 2023)
This study aims to find out the types of cooperative principle maxims according to Grice's theory which were used in an interview on the 8th of September 2021 edition of the television show "Quotidien". The main theory used in this research is the cooperative principle theory put forward by Grice, (1989). The research method used in this research is the “analisis isi”. The analysis activities carried out are collecting data by watching videos of data sources, classifying data based on the use of the maxims of the cooperative principle, and analyzing the use of the maxims of the cooperative principle based on the main theory. The results of the study show that there are 30 datas using Grice's cooperative maxims, where it is found the use of Grice's cooperative maxims. The uses found are the maxim of quality, maxim of quantity, and maxim of manner. The finding of the use of the maxim of cooperative principle is dominated by the use of the maxim of quality with a total of 14 speech events, the use of the maxim of quantity with a total of 8 speech events, then the use of the maxim of relevance with a total of 2 speech events. The use of Grice's maxim of cooperative principle that was not found was the use of the maxim of manner